The pirate pig - Funke, Cornelia, 1958-; Latsch, Oliver; Meyer, Kerstin, 1966- (New York Random House, 2015)
On Butterfly Island, sailer Stout Sam and his deckhand Pip must rescue their treasure-sniffing pig from nasty pirate Barracuda Bill.
"Originally published as Das Piratenschwein by Cecilie Dressler Verlag GmbH & Co. KG, Hamburg, Germany, in 1999"--Copyright page.
b
b
Keywords: Pigs -- Fiction; Pirates -- Fiction; Buried treasure -- Fiction; Islands -- Fiction